The Implementation of Talent Management Implementation at Regional Employee Agency Wonogiri Regency Central Java - Ambarawati, Ni Gusti Made Ayu; Wijoyo, Risang Priyo (Institut Pemerintahan Dalam Negeri, 2023)
Bureaucratic Reform (RB) in Indonesia represents a strategic redesign of the bureaucratic system to adapt to societal and global dynamics. Within the spectrum of RB-induced changes, particular attention is given to human resources, with Talent Management emerging as a pivotal element aimed at enhancing the governance of civil servants (ASN). This research seeks to explore the implementation of Talent Management in the Regional Employee Agency (BKD) of Wonogiri Regency, examining both supporting and inhibiting factors, and proposing solutions in line with Policy Implementation theory. Employing qualitative research methods encompassing observation, interviews, and documentation, the study reveals that the implementation of Talent Management in Wonogiri Regency is generally commendable, driven by effective communication, the commitment of the Wonogiri Regent, and clear Standard Operating Procedures (SOPs). Nevertheless, challenges include the absence of assessors, lack of an Assessment Center, insufficient budget allocation, and the absence of a dedicated field for Talent Management. Mitigation efforts involve certifying assessor employees, proposing the construction of an Assessment Center, requesting budget allocations, and refining the organizational structure to address these challenges and further enhance the Talent Management framework.